2014
DOI: 10.1111/jerd.12127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender, Anxiety and Depression Symptoms, and Use of Oral Contraceptive in Color Perception

Abstract: The ability to understand and distinguish color differences is extremely important in clinical dentistry. There could be differences in color perception between men and women that would influence clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
1
21
2
Order By: Relevance
“…Unlike the findings of the present study, most studies reported no significant influence of gender on VSM. However, the experimental design of these studies used shade tabs from specific shade guides to match a target shade tab or matching pairs of monochromatic ceramic specimens . From the studies reporting significant influence of gender on VSM, only two of them matched natural teeth to a specific shade guide, which simulates clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the findings of the present study, most studies reported no significant influence of gender on VSM. However, the experimental design of these studies used shade tabs from specific shade guides to match a target shade tab or matching pairs of monochromatic ceramic specimens . From the studies reporting significant influence of gender on VSM, only two of them matched natural teeth to a specific shade guide, which simulates clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The gender influence on the accuracy of visual shade matching is controversial. Some studies reported a better performance from males, others favored females, and many studies showed no evidence of gender influence on VSM …”
Section: Introductionmentioning
confidence: 99%
“…Color perception might be affected by color vision deficiency. It has been found that genetic color vision deficiency affects about 8% of males and about 2% of females . Ishihara pseudoisochromatic plates were used as screening tools for deficiencies in red–green color vision.…”
Section: Discussionmentioning
confidence: 99%
“…A visual shade‐matching assessment is an act that involves the observer's eye. It is a process where multiple factors such as age, gender, emotion, fatigue, physiological factors (color deficiency), experience, education, and training can play a role in the observer's perception . Among these factors, education and training have been found to be the most influential ones …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation